2007
DOI: 10.1097/fpc.0b013e328256b1b6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mutations associated with Gilbert and Crigler–Najjar type II syndromes on the glucuronidation kinetics of bilirubin and other UDP-glucuronosyltransferase 1A substrates

Abstract: The glucuronidation of all UGT1A1 substrates is likely to be impaired in subjects carrying the UGT1A1*6 and UGT1A1*62 alleles, although the reduction in metabolic clearance might vary with the substrate. The Y486D mutation appears to greatly reduce most, but not all, UGT1A activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 40 publications
6
72
0
7
Order By: Relevance
“…Consistent with previous reports (Fisher et al, 2001;Udomuksorn et al, 2007), in the present study estradiol-3-glucuronidation exhibited a sigmoidal kinetic profile. A widely accepted mechanism for sigmoidal kinetics involves cooperative binding of multiple substrate molecules to the enzyme (Segel, 1975;Korzekwa et al, 1998;Shou et al, 2001;Houston and Galetin, 2005).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous reports (Fisher et al, 2001;Udomuksorn et al, 2007), in the present study estradiol-3-glucuronidation exhibited a sigmoidal kinetic profile. A widely accepted mechanism for sigmoidal kinetics involves cooperative binding of multiple substrate molecules to the enzyme (Segel, 1975;Korzekwa et al, 1998;Shou et al, 2001;Houston and Galetin, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…In further support of the use of estradiol-3-glucuronidation as a measure of UGT1A1, beyond avoiding the technical challenges involved in measuring bilirubin glucuronidation, estradiol-3-glucuronide is commercially available and is easily measured. However, estradiol-3-glucuronidation has been reported to exhibit autoactivation (homotropic cooperativity) in human liver microsomes and recombinant UGT1A1 (Fisher et al, 2001;Udomuksorn et al, 2007). Atypical kinetic profiles, classified by homotropic and heterotropic cooperativity, have been increasingly reported with UGTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blotting-Proteins in lysates from HEK293T cells stably expressing wild-type and mutant UGT3A cDNAs were separated on SDS-polyacrylamide gels and transferred to nitrocellulose membranes as described previously (8,15). Wild-type and mutant UGT3A proteins were detected with anti-UGT3A1 and anti-UGT3A2 antibodies generated previously (8,9) and a peroxidase-conjugated goat anti-rabbit secondary antibody (NeoMarkers).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of bilirubin glucuronidation suggested that diglucuronide formation may be carried out by UGT tetramers [31]. Expressed human UGT1A1 efficiently converts the two bilirubin monoglucuronides (at either the C8 or C12 propionic acid group) to the diglucuronide [32], and bilirubin is known to be mainly secreted in human bile as the diglucuronide.…”
Section: Diglucuronide Formation By Ugt Tetramersmentioning
confidence: 99%